VD_FINDINFO Jug / 2020 / 433 vom 28. Juni 2021 - VD Tribunal cantonal (2021)
COORDINATIONASSURANCE, INDEMNITÉEN GÉNÉRAL, CONCORDANCE | 150 CO, 42 al. 2 CO, 46 CO, 51 CO, 3 CPC, 58 LCR, 61 LCR, 62 LCR, 65 LCR, 72 LPGA, 82 al. 1 LPGA, 34 LPP, 27 OPP2